Clinical Predictors of Response to Baclofen in the Treatment of Alcohol use Disorder: Results from the BacALD Trial. (12th April 2019) - Rombouts, Susan A; Baillie, Andrew; Haber, Paul S; Morley, Kirsten C
Abstract: Aim: To examine clinical predictors of treatment response to baclofen in patients with alcohol use disorder (AUD). Methods: Data from a randomised controlled trial (RCT) ( N = 104), in which AUD patients received placebo or baclofen (30 mg/day or 75 mg/day) for 12 weeks, were analysed to determine predictive effects of the following four clinical characteristics: alcoholic liver disease (ALD), baseline alcohol consumption, craving and anxiety. Treatment outcomes included: (i) time to lapse and (ii) time to relapse. Results: For both outcome measures, baclofen, irrespective of dose, was more effective when alcohol consumption was higher at baseline. Relative to placebo, baclofen increased time to first lapse in patients with higher baseline alcohol consumption (HR = 0.459, 95% CI = 0.219–0.962, P < 0.05). Similarly, baclofen increased time to first relapse in patients with higher alcohol consumption at baseline (HR = 0.360, 95% CI = 0.168–0.772, P < 0.05). There were no predictive effects of other baseline characteristics on time to lapse nor time to relapse. Directly comparing high dose of baclofen (75 mg/day) with low dose of baclofen (30 mg/day) revealed no differences with regards to predictors of baclofen response. Conclusion: Baclofen, relative to placebo, was more effective when alcohol consumption was higher at baseline.